Prevalence of Open Defecation Practice and Associated Factors Poverty and Geography in Palembang Indonesia - Yuliana, Evi; Susetyo, Didik; Yamin, Muhammad; Antoni, Mirza (Journal of Ecohumanism, 2024)
Palembang is one of the large cities in Indonesia which has a specific geography. A study was conducted to estimate the prevalence and determine poverty factors associated with open defecation practices.An analytical cross-sectional study was conducted for one year among 397 respondents as a sampling. Prevalence was calculated with 95% confidence intervals and binary logistic regression analysis was performed to determine factors associated with open defecation.32.5 percent of people still practice open defecation which is influenced by poverty and geographical factors. Influence of income ) AOR of 13,891 (Cl 8,345 – 23,123), education AOR of 20,328 (Cl 11,881 – 34,780), clean AOR 6,192 (Cl 3,747 – 10,234), water source AOR of 28,882 (16,403 - 50,854), characteristics of the house AOR of 3,977 (2,555 – 6,191), facilities or the availability of toilets at home AOR of 7,066 (4,167 – 11,983), geographical location of the house towards the river or water AOR of 478.995 (173.112 – 1325.1399), knowledge of open defecation behavior AOR of 3.607 , attitudes AOR of 3.277. Respondents who practice open defecation have low income and education, no water source available from the government, geographical location of the house near a river or swamp, no defecation facilities, lack of knowledge and bad behavior.